2020
DOI: 10.1002/brb3.1549
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial, viral, and fungal infection‐related risk of Parkinson's disease: Meta‐analysis of cohort and case–control studies

Abstract: Aims Recent studies showed that patients with various bacterial, viral, and fungal infections might be at increased risk of Parkinson's disease (PD). However, the risk of PD in patients with each specific infection varied. This meta‐analysis estimated the association between various infections and PD risk. Methods Literature published from January 1965 to October 2019 in PubMed and EMBASE databases was searched. Data were extracted and pooled using random/fixed effects model. Sensitivity analysis and meta‐regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 56 publications
(101 reference statements)
3
58
1
3
Order By: Relevance
“…In that context, a recent meta-analysis that included 23 studies investigated the impact of viral, fungal, and bacterial infections in the risk of PD and found a positive association between H. pylori infection and that disease (pooled OR, 95%CI: 1.653, 1.426-1.915, P < 0.001)[ 118 ]. Furthermore, another meta-analysis which included 7 studies found that the H. pylori infection is also associated with the clinical severity of the PD, since H. pylori -positive patients presented poorer scores when undergone Unified Parkinson Disease Rating Scale (UPDRS) evaluation [mean ± SD, 95%CI: 6.83, 2.29-11.38, P = 0.003][ 119 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In that context, a recent meta-analysis that included 23 studies investigated the impact of viral, fungal, and bacterial infections in the risk of PD and found a positive association between H. pylori infection and that disease (pooled OR, 95%CI: 1.653, 1.426-1.915, P < 0.001)[ 118 ]. Furthermore, another meta-analysis which included 7 studies found that the H. pylori infection is also associated with the clinical severity of the PD, since H. pylori -positive patients presented poorer scores when undergone Unified Parkinson Disease Rating Scale (UPDRS) evaluation [mean ± SD, 95%CI: 6.83, 2.29-11.38, P = 0.003][ 119 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
“…Last but not least, H. pylori infection is closely related to various socioeconomic factors, including hygiene. Consequently, some of the associations between H. pylori and PD could have been correlational and not causal[ 118 , 119 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the acceleration of the population aging process and decrease of physical functions of senile patients, the incidence and prevalence of PD have shown an increasing trend year by year (Nussbaum and Ellis, 2003;Hirsch et al, 2016). Approximately between 4.1 million and 4.6 million people are affected by PD in 2005 totaled, and it has been estimated that number will more than double by 2030 to between 8.7 million and 9.3 million in the most populous nations (Dorsey et al, 2007;Wang et al, 2020). The majority of people who get PD are over the age of 60, the incidence of PD among people over 60 is about one percent, men are more susceptible to PD than women at a ratio of about 3:2 (De Lau and Breteler, 2006;Dorsey and Bloem, 2018;Cerri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%